Pembangunan Desa Mandiri Melalui Badan Usaha Milik Desa: Studi Kasus Desa Tiremenggal - Anshori, M. Shofi; Syafi'i, Muhammad Aris; Devi, Happy Sista (Sekolah Tinggi Agama Islam (STAI) Ki Ageng Pekalongan, Indonesia, 2024)
Village is a fundamental community unit in Indonesia's development landscape. However, many villages still face significant challenges, such as poverty, lack of community participation, and low social capital. To address these issues, the Indonesian government has introduced various programs, including the Independent Village Program managed by Village-Owned Enterprises (BUMDES). This research employs a qualitative descriptive approach to analyze BUMDES management strategies in realizing independent villages, with a focus on Tiremenggal Village in East Java. Through the analysis of strategic management, implementation of BUMDES strategies, and evaluation of strategies conducted in this research, it is found that Tiremenggal Village has successfully utilized natural resources and human resources to enhance social, economic, and environmental resilience. BUMDES has been instrumental in advancing this village through various development programs and projects, as well as increasing community involvement in village management. However, the research also identifies several inhibiting factors, such as differences in understanding and opinions within the community, as well as the need to improve the quality of human resources. In conclusion, the development of independent villages requires cooperation between the government, BUMDES, and the community. By leveraging local potentials and addressing existing barriers, villages in Indonesia can achieve sustainable prosperity and self-reliance.